التأمين التكافلي الإسلامي: أحكامه الشرعية وأهميته الاقتصادية والاجتماعية - حميش عبد الحميد; حارك حسام (جامعة محمد بوضياف – المسيلة–, 2025)
تسعى هذه الدراسة إلى استعراض التأمين التكافلي الإسلامي من خلال تحليل أسسه الشرعية وأهميته الاقتصادية والاجتماعية، مركزة على طبيعة عقد التأمين التكافلي واختلافه الجوهري عن التأمين التجاري التقليدي الذي غالباً ما يشوبه الغرر والربا. تبرز أهمية التأمين التكافلي كرافد أساسي في التمويل الإسلامي، إذ يعتمد على مبادئ التعاون والتكافل ويوفر حماية مالية مشروعة للأفراد والمؤسسات، مما يسهم في تحقيق الاستقرار المالي والاجتماعي، لا سيما في الدول الإسلامية التي تسعى إلى تطوير أنظمة مالية متوافقة مع الشريعة. تتناول الدراسة مفهومالتأمين التكافلي وخصائصه، وتحلل أسسه الفقهية، وتستعرض الأحكام العملية لإدارة الاشتراكات والتعويضات واستثمار أموال الصندوق وفق الضوابط الشرعية. كما ترصد أهمية التأمين التكافلي في التنمية الاقتصادية والاجتماعية من خلال التجارب الدولية والعربية، مع التركيز على الواقع الجزائري وتحدياته مثل ضعف الوعي التأميني، محدودية المنتجات، نقص الكفاءات، وتأخر الرقمنة، إلى جانب الفرص المتاحة للنمو. أظهرت نتائج الدراسة أن التأمين التكافلي نظام تعاوني مبني على التبرع، ويختلف عن التأمين التجاري في الأساس العقدي والرقابة الشرعية، وقد ساهم في دول مثل ماليزيا والسودان في نمو سوق التأمين، ورفع معدلات الادخار والاستثمار، وتعزيز الشمول المالي، ودعم الفئات الضعيفة، وتقليل الفقر والبطالة. أما في الجزائر، فما زال القطاع يواجه تحديات رغم التطور التشريعي، مع وجود فرص للنمو من خلال زيادة الطلب على المنتجات المالية الإسلامية، دخول شركات جديدة، التحول الرقمي، والاستفادة من التجارب الدولية. تخلص الدراسة إلى أن التأمين التكافلي يمثل منظومة متكاملة تحقق التكافل الاجتماعي والعدالة، وتستجيب لحاجات المجتمع في الحماية المالية والتنمية المستدامة، مع ضرورة تذليل العقبات التشريعية والثقافية لضمان فعاليته واستدامته في الجزائر. كلمات مفتاحية: التأمين التكافلي، الأحكام الشرعية، الأهمية الاقتصادية، الأهمية الاجتماعية، الأفاق المستقبلية. Abstract: This research aims to examine Islamic Takaful insurance by analysing its Sharia foundations and its economic and social significance, with particular attention to the nature of the Takaful contract and its fundamental differences from conventional insurance, which is often associated with uncertainty (gharar) and usury (riba). The study highlights the importance of Takaful as a core component of Islamic finance, emphasizing its basis in cooperation and mutual solidarity, and its role in providing legitimate financial protection for individuals and institutions. This contributes to financial and social stability, especially in Muslim-majority countries seeking to develop financial systems in line with Sharia principles. The study explores the concept and characteristics of Takaful, analyses its jurisprudential underpinnings, and reviews the practical rulings governing the management of contributions, claims, and fund investments according to Sharia guidelines. It also assesses the role of Takaful in economic and social development through international and Arab experiences, with a special focus on the Algerian context—identifying challenges such as low insurance awareness, limited product offerings, skills shortages, and delays in digital transformation, alongside available growth opportunities. Findings indicate that Takaful is a cooperative system rooted in voluntary giving (tabarru’), fundamentally distinct from commercial insurance in its contractual structure and Sharia oversight. In countries like Malaysia and Sudan, Takaful has contributed to the expansion of the insurance market, increased savings and investment rates, enhanced financial inclusion, supported vulnerable groups, and helped reduce poverty and unemployment. In Algeria, despite recent legislative progress, the sector still faces challenges, though it benefits from rising demand for Islamic financial products, new market entrants, digital transformation, and the potential to learn from international best practices. The study concludes that Takaful is not merely a technical alternative to conventional insurance, but a comprehensive system that fosters social solidarity and justice, meets the financial protection needs of society, and supports sustainable development. Overcoming legislative and cultural barriers is essential to ensuring its effectiveness and long-term viability in Algeria. Keywords: Takaful insurance, Sharia rulings, economic importance, social importance, future prospects.